ChemInform Abstract: Domino Reactions for the Synthesis of Anthrapyran‐2‐ones and the Total Synthesis of the Natural Product (.+‐.)‐BE‐26554A. Issue 6 (11th February 2014) - Rixson, James E.; Skelton, Brian W.; Koutsantonis, George A.; Gericke, Kersten M.; Stewart, Scott G.
Abstract This straightforward approach gives access to a new series of anthrapyran‐2‐ones as well as to the antibiotic and antitumor compound (XII).